2021
DOI: 10.3389/fpubh.2021.622809
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking the Top-Down Approach to Schistosomiasis Control and Elimination in Sub-Saharan Africa

Abstract: The control and elimination of schistosomiasis have over the last two decades involved several strategies, with the current strategy by the World Health Organization (WHO) focusing mainly on treatment with praziquantel during mass drug administration (MDA). However, the disease context is complex with an interplay of social, economic, political, and cultural factors that may affect achieving the goals of the Neglected Tropical Disease (NTD) 2021-2030 Roadmap. There is a need to revisit the current top-down and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…Uptake of MDA in Uganda has been compromised by a lack of knowledge about schistosomiasis transmission and prevention [ 5 , 22 ], a lack of knowledge about the MDA programme itself [ 18 ], and assumptions that MDA is only for children [ 18 ]. There is a call to rethink the top-down approach to schistosomiasis control, and making sure that people are correctly informed about the disease, its transmission, and the treatment available for it, will be key to giving people ownership over the problem [ 23 , 24 ]. Despite control efforts in endemic areas in Uganda, little is known about which schistosomiasis messages are presented, and to whom, and how they are perceived by community members.…”
Section: Introductionmentioning
confidence: 99%
“…Uptake of MDA in Uganda has been compromised by a lack of knowledge about schistosomiasis transmission and prevention [ 5 , 22 ], a lack of knowledge about the MDA programme itself [ 18 ], and assumptions that MDA is only for children [ 18 ]. There is a call to rethink the top-down approach to schistosomiasis control, and making sure that people are correctly informed about the disease, its transmission, and the treatment available for it, will be key to giving people ownership over the problem [ 23 , 24 ]. Despite control efforts in endemic areas in Uganda, little is known about which schistosomiasis messages are presented, and to whom, and how they are perceived by community members.…”
Section: Introductionmentioning
confidence: 99%
“…Second, our results confirmed that the ‘bottom-up’ approach enhances capacity building, sensitization, and behaviour change as catalysts for improved uptake of NTD interventions since they involve forming active community committees comprising of health workers, CHVs, and individuals for health purposes, education and NTD surveillance. Comparatively, Onasanya et al [ 66 ] report that an active approach to NTD control in SSA requires dynamic and diversified bottom-up processes that involve multiple stakeholders and paves the way for the achievement of the NTD 2021–2030 goals. An increased social capital within the community and between the community and the national health system may lead to better health outcomes [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, schistosomiasis control efforts have centered on strategies ranging from disease treatment to managing complications and limiting disease spread through various public health efforts such as health education, snail intermediate host control, and water, sanitation and hygiene (WASH) programs [8][9][10]. The effect of the targets set by the World Health Organization for global schistosomiasis control, based on large-scale mass drug administration (MDA) of praziquantel (PZQ), has been suboptimal due to a myriad of logistical challenges, including a shortfall in drug delivery and adherence, sustained reinfection rates and inadequate infrastructure [11][12][13][14]. While these MDA programs have been somewhat effective in the short term, they are, however, unsustainable in the long term.…”
Section: Introductionmentioning
confidence: 99%